Photoreduction of Azaoxoisoaporphines by Amines: Laser Flash and Steady‐State Photolysis and Pulse Radiolysis Studies1. (10th June 2013) - de la Fuente, Julio R.; Aliaga, Christian; Cañete, Alvaro; Kciuk, Gabriel; Szreder, Tomasz; Bobrowski, Krzysztof
Abstract: Photoreduction of 7 H ‐benzo[ e ]perimidin‐7‐one (3‐AOIA, A1) and its 2‐methyl derivative (2‐Me‐3‐AOIA, A2) by non‐H‐donating amines (1, 4‐diazabicyclo[2.2.2]octane [DABCO]; 2, 2, 6, 6‐tetramethylpiperidine [TMP]), and a hydrogen‐donating amine (triethylamine [TEA]), has been studied in deaerated neat acetonitrile solutions using laser flash photolysis (LFP) and steady‐state photolysis. The triplet excited states of A1 and A2 were characterized by a strong absorption band with λ max  = 440 nm and lifetimes of 20 and 27 μs respectively. In the presence of tertiary amines, both triplet excited states were quenched with rate constants close to the diffusional limit ( k q ranged between 10 9 and 10 10  M −1  s −1 ). The transient absorption spectra observed after quenching with DABCO and TMP were characterized by maxima located at 460 nm and broad shoulders in the range of 500–600 nm. These transient species are attributed to solvent‐separated radical ion pairs and/or to isolated radical anions. In the presence of TEA, these transients undergo proton transfer, leading to the neutral hydrogenated radicals, protonated over the N1‐ and O‐atoms. Transient absorption spectra of these transients were characterized by maxima located at 400 and 520 nm and 430 nm respectively. Additional support for these spectral assignments was provided by pulse radiolysis (PR) experiments in acetonitrile and 2‐propanol solutions. Abstract : Photoreduction of 7 H ‐benzo[ e ]perimidin‐7‐ones by amines proceeds through a stepwise electron‐proton‐electron transfer mechanism, which was studied by using laser flash photolysis, steady‐state photolysis and pulse radiolysis. Later, to achieve the triplet state, the sequence of reaction generates a radical ion pair, which by proton transfer over the N1‐ and O‐atoms of substrates yields two different hydrogenated radicals, likely in equilibrium. These neutral radicals by the second electron transfer lead to the metastable products. Transient absorptions for intermediaries were characterized by laser flash photolysis and pulse radiolysis.